2017
DOI: 10.1016/j.vaccine.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Demand- and supply-side determinants of diphtheria-pertussis-tetanus nonvaccination and dropout in rural India

Abstract: BackgroundAlthough 93% of 12- to 23-month-old children in India receive at least one vaccine, typically Bacillus Calmette–Guérin, only 75% complete the recommended three doses of diphtheria-pertussis-tetanus (DPT, also referred to as DTP) vaccine. Determinants can be different for nonvaccination and dropout but have not been examined in earlier studies. We use the three-dose DPT series as a proxy for the full sequence of recommended childhood vaccines and examine the determinants of DPT nonvaccination and drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 49 publications
3
45
0
Order By: Relevance
“…Many earlier studies from India have conducted similar analyses combining immunization information based on maternal recall and vaccination cards and in our study, a vast majority of the unvaccinated children (89%) would have been excluded if the analyses were restricted to information based on maternal recall alone [7,12,22,23,26,28,44,45]. Third, a recent study observed age misreporting and likely underreporting of recent pregnancies among female respondents, highlighting potential selection and information biases in large scale surveys such as the DLHS [46].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Many earlier studies from India have conducted similar analyses combining immunization information based on maternal recall and vaccination cards and in our study, a vast majority of the unvaccinated children (89%) would have been excluded if the analyses were restricted to information based on maternal recall alone [7,12,22,23,26,28,44,45]. Third, a recent study observed age misreporting and likely underreporting of recent pregnancies among female respondents, highlighting potential selection and information biases in large scale surveys such as the DLHS [46].…”
Section: Discussionmentioning
confidence: 62%
“…Previous research from India tends to highlight socio-demographic characteristics associated with uptake such as child's gender, order of birth, place of delivery, maternal age at childbirth, parental education, caste and religious preference, household wealth and location (urban or rural) , [6][7][8]11,12]. Of late, non-socio-demographic demand-side issues such as awareness regarding the need for and timing of routine childhood vaccinations, fears regarding some or all routine vaccines and parental beliefs regarding false contraindications to routine vaccinations have been reported as reasons linked to partialvaccination and non-vaccination of Indian children [4, 12,13]. As, the Indian Government aims to boost full immunization coverage of UIP vaccines to 90% through the Mission Indradhanush initiative by 2020, it is important to track the various socio-demographic and non-socio-demographic factors influencing suboptimal vaccination over the years to identify key areas of intervention and further research.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surprising because our model took into account mostly demand-side determinants. However, various studies documented several supply-side factors as a predictor for immunization coverage [9,10,[72][73][74], such as cold chain management, vaccine availability, and adequacy of staffing which we are not able to include in our model due to lack of such information in the dataset we used. Moreover, there may be other demand-side factors that could be associated with underlining socio-economic inequality and that need to be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are several classifications made by researchers to classify determinants of vaccine uptake. Ghosh et al [ 6 ] classify immunization coverage factors in two categories according to their literature review, supply-side and demand-side. According to their research demand-side factors covers birth order, sex, maternal education, and employment status, occupation type, immunization related beliefs, mother’s health knowledge, health-seeking behavior, household wealth index, religion, and caste.…”
Section: Literature Reviewmentioning
confidence: 99%